Active listening for effective student engagement - Angela Newton (Journal of Learning Development in Higher Education, 2024)
Active listening can play a key and positive role in our relationships with others (Wolvin and Coakley, 2000; Bodie, 2011; Ellis and Abbot, 2018). When we fail to listen, we risk a lack of trust, empathy and insight; all crucial in effective communication. Whilst a lot of literature focuses on how active listening benefits students who use it, there is less understanding of the role of learning developers and the value of their actively listening to students (Canpolat et al., 2015; Shernof, et al., 2017; Eggenburger, 2021). Active listening by learning developers is, I would argue, vital in order to properly engage with and understand students. Utilising active listening in for example, 1-2-1 situations, may give students more confidence to express themselves and improve their relationship with and perception of their educational experience (Locktie, 2018). True active listening requires the listener to tune into the words of another person and suspend their assumptions (Lipari, 2010); embracing ‘listening being’ in our learning development practice may create a more positive student experience by building a person-centred atmosphere (Lipari, 2010). With discussions around the importance of developing a ‘sense of belonging’ in students gaining traction even before the COVID-19 pandemic, active listening deserves more attention. Moreover, in the context of high workloads and the increasing pressures of our higher education system, active listening is a neglected area of personal and professional development (Wolvin and Coakley, 2012). In this workshop, participants discussed how active listening can enhance their interactions with students whether online or in person. We refined our skills through practical, reflective activities, with a focus on the issues that impede our ability to listen and how we can improve. We also considered how listening feels from different perspectives and what kinds of behaviours we expect from a listener.